1992
DOI: 10.1097/00000658-199201000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors Influencing Survival in Gastrointestinal Leiomyosarcomas Implications for Surgical Management and Staging

Abstract: The appropriate surgical therapeutic options for either localized or more advanced disease in patients with gastrointestinal leiomyosarcomas remain unclear. A staging classification for this disease has not been adopted nor risk factors identifying patients at risk for recurrence defined. To address these issues, this study evaluated the influence of various clinicopathologic variables on overall and disease-free survival. In an univariate analysis of overall survival involving 191 patients, the Cox proportion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

19
300
6
27

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 390 publications
(352 citation statements)
references
References 10 publications
19
300
6
27
Order By: Relevance
“…There is a strong need for a practical and reliable classification system that can be used to predict the clinical course of GIST patients and facilitate the design of treatment regimen. On the basis of previous investigations and our preliminary work, [10][11][12][13][14][15][16][17][18] we collected the pathological and clinical data of a large number of GIST patients and assessed a simple and new grading and staging system. Patients from multiple hospitals were analyzed because it is expected to be more likely free of selection bias, which could occur in different hospitals or treatment trials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a strong need for a practical and reliable classification system that can be used to predict the clinical course of GIST patients and facilitate the design of treatment regimen. On the basis of previous investigations and our preliminary work, [10][11][12][13][14][15][16][17][18] we collected the pathological and clinical data of a large number of GIST patients and assessed a simple and new grading and staging system. Patients from multiple hospitals were analyzed because it is expected to be more likely free of selection bias, which could occur in different hospitals or treatment trials.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first time that the degree of malignancy was demonstrated by the number of the predictive parameters of malignancy. Previous studies have demonstrated that the adverse outcome of GISTs correlates with the increase in the tumor size, 12,16,25,[50][51][52][53] mitotic rate, 20,25,51,52,54 cellularity 51,52,55 and nuclear atypia. 16 In addition, tumor site 23,56,57 from the upper to lower GI tract seemingly had an effect on the outcome too.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Gastric resection without lymph node dissection in the treatment of malignant neoplasm (such as leiomyosarcoma) may be controversial although studies have demonstrated no benefit from the addition of systemic lymph node dissection or more extensive resection in the treatment of leiomyosarcoma. 8,9 These results are important when considering the laparoscopic technique for any gastric stromal tumor resection because often the diagnosis of leiomyosarcoma versus leiomyoma may not be evident until after resection. In fact, biopsies from endoscopy yield the diagnosis in less than 60% of the time.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Although some authors feel that more extensive resections may be necessary for high-grade leiomyosarcoma, 12 others believe that a wedge resection is sufficient for leiomyosarcomas. 8,9 Four major laparoscopic methods have been described for the resection of gastric leiomyoma. The choice of technique should be based both on size and location of the lesion.…”
Section: Discussionmentioning
confidence: 99%